Peran UKM dalam Memposisikan Produk Khas Daerah melalui Manajemen Image di Era Persaingan Global - Maryati, Wiwik (BISMA (Bisnis dan Manajemen), 2018)
This study aimed to investigate the role of SMEs on local product positioning through image management in this current global competitive era. SMEs have played a role, particularly to local products to be globally well recognized as featured products. Jombang is one of region in East Java which has a lot of SMEs that has successfully produced various local products such as foods, beverage, handycrafts, and batik. For this far, a lot of their products have widely reached customers across the globe. However, some people remain unfamiliar with those local products, since many of the SMEs did their marketing indirectly. Therefore, it needs a management of image to build valuation and gain customers trust entirely. This present study applied a qualitative approach with case study as its research method by examining the conditions of SMEs in Jombang. The result showed that the SMEs played their role in positioning various local products in this current global competitive era through a management of image, both in brands and the SMEs. The management of image was conducted by communicating the marketing through various media, both electronic and non-electronic ones, in order to get better understanding about consumers. This present study, however, has limitation on the number of the entrepreneurs selected as the participants of this research. Thus, it is interesting for further studies to conduct their researches not only on limited particular enterprises, but more.